ERHVERVSMAGI? Om charlatanisme og værdiskabelse ud af den blå luft - Salamon, Karen Lisa (Tidsskriftet Antropologi, 2010)
The author argues for the relevance of applying ethnographic theories of sociality, magic and trickster to empirical data and discourse on contemporary economic value creation and so-called “financial wizardry”. Salamon discusses contemporary cases of massive financial fraud as instances of illusionism that draw on similar social and significant mechanisms as did the performances of historical charlatans and magicians. The article draws on publicly accessible information and media coverage on two recent cases of substantial financial fraud, a historical analysis of charlatanism in medieval Italy, as well as classic ethnographic theories of magic. The argument relates the fraud cases to analyses of alchemical reasoning and occultism and points out that charlatanism, magic illusionism and grand financial fraud all profit from being “too good to be true” and “too cheap for the price”. The cases are supernatural because their price and value stem from doing “the impossible”. They seduce their audiences by the trick of the “cure all – no risk – something out of nothing” financial performance, just as the illusionist’s audiences are seduced by his impossible trick of pulling several large doves up from one small hat. Salamon concludes that the “financial wizard’s” claim to virtual, and rather Effortless, conjuring up of economic value resembles general value creation under contemporary financial capitalism, resonating magic: The “white magic” of contemporary financial capitalism only turns out to be defined as “black magic” when it – after the fact - carries negative results for its investors, audiences – and performers. Keywords: Anthropology of management, fraud, theories of magic, theory of value, charlatanism, trickster.